2023
DOI: 10.3390/nu15020273
|View full text |Cite
|
Sign up to set email alerts
|

Immune System and Epidemics: The Role of African Indigenous Bioactive Substances

Abstract: With over 6 million coronavirus pandemic deaths, the African continent reported the lowest death rate despite having a high disease burden. The African community’s resilience to the pandemic has been attributed to climate and weather conditions, herd immunity, repeated exposure to infectious organisms that help stimulate the immune system, and a disproportionately large youth population. In addition, functional foods, herbal remedies, and dietary supplements contain micronutrients and bioactive compounds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 223 publications
0
0
0
Order By: Relevance
“…Further 134 documents were excluded after the analysis of abstracts as they did not meet at least one of the eligibility/inclusion criteria: 53 did not deal with Africa; 69 dealt with other species of moringa, e.g., Moringa stenopetala , Moringa peregrina , or Moringa ovalifolia (articles dealing with Moringa pterygosperma , which is considered erroneously a synonym of M. oleifera , were considered eligible); and 12 were editorial materials. Finally, the analysis of full texts led to the exclusion of 103 documents, including 47 reviews [ 35 , 37 , 38 , 41 , 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 67 , 70 , 71 , 72 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further 134 documents were excluded after the analysis of abstracts as they did not meet at least one of the eligibility/inclusion criteria: 53 did not deal with Africa; 69 dealt with other species of moringa, e.g., Moringa stenopetala , Moringa peregrina , or Moringa ovalifolia (articles dealing with Moringa pterygosperma , which is considered erroneously a synonym of M. oleifera , were considered eligible); and 12 were editorial materials. Finally, the analysis of full texts led to the exclusion of 103 documents, including 47 reviews [ 35 , 37 , 38 , 41 , 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 67 , 70 , 71 , 72 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Methodsmentioning
confidence: 99%
“…Still, they remain debated due to a lack of conclusive evidence from clinical trials. Bioactive substances from indigenous African foods have also been linked to an observed high immunity of the population [7]. Using bacterial isolates of plant origin, a body of research has identified desirable metabolic effects that can take place during fermentation (Table 2).…”
Section: Impact Of Lactic Acid Fermentation On Macronutrients and Rel...mentioning
confidence: 99%
“…Flavour and texture are tightly linked with consumer acceptance and typically serve as a focal point during product developments. In traditional foods, fermentation is, however, increasingly being recognised for its health-beneficial impact on nutrient bioavailability and the accumulation of bioactive metabolites, which likely contributed to the popularity and historic adoption of traditional fermented foods [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%